2008
DOI: 10.4196/kjpp.2008.12.6.337
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Ion Channels in Human Bone Marrow Mesenchymal Stem Cells from Amyotrophic Lateral Sclerosis Patients

Abstract: was also recorded. In the RT-PCR analysis, Kv1.1, heag1, Kv4.2, Kir2.1, M axiK, and hNE-Na were detected. In particular, INa,TTX showed a significant passage-dependent increase. This is the first report showing that functional ion channel profiling depend on the cellular passage of hBM-MSCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…, Park et al . ). In these studies, IK dr and I to , being time and voltage dependent, and IBK Ca were described.…”
mentioning
confidence: 97%
“…, Park et al . ). In these studies, IK dr and I to , being time and voltage dependent, and IBK Ca were described.…”
mentioning
confidence: 97%
“…Furthermore, osteoblasts and osteocytes possess ion channels and channels have different functions. It has been reported that K + and Ca ++ channels have roles in proliferation, differentiation and apoptosis (Tao et al, 2008), in the modulation of the progression of the cell cycle and in affecting the proliferation of MSCs (Wang et al, 2008) (Park et al, 2008). There is a variable expression of K + channel with cell cycle of MSCs and this way contributes to the cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%
“…profiling may depend on the cellular passage of MSCs (Park et al, 2008 (Zahanich et al, 2005) (Zahanich et al, 2005;Balana et al, 2006;Zeng et al, 2011) (Zahanich et al, 2005) (Zahanich et al, 2005) (Li et al, 2006) (Li et al, 2006Park et al, 2007;Park et al, 2008) (Li et al, 2006;Park et al, 2007) (Park et al, 2007) (Magra et al, 2007) (Magra et al, 2007) (Magra et al, 2007) (Heubach et al, 2004Balana et al, 2006;Park et al, 2007;Bonnet et al, 2008;Park et al, 2008) (Bonnet et al, 2008Wang et al, 2008;Wang et al, 2009;Zeng et al, 2011) (Li et al, 2005Zeng et al, 2011) (Balana et al, 2006;Bonnet et al, 2008) (Zahanich et al, 2005;Bergh et  al., 2006)(Gu et al, 2001;Zahanich et al, +++ 2005;Bergh et al, 2006)(Gu et al, 2001;Bergh et al, 2006) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Outros estudos ressaltaram que a liberação de fatores neurotróficos pelas células enxertadas seriam capazes de promover a remielinização de oligodendrócitos, incrementar a proliferação dos astrócitos e estimular o surgimento de novas fibras nervosas, o que contribuiria para a melhora da função neurológica 17 . Park e colaboradores comprovaram a capacidade das células-tronco embrionárias, e suas derivadas, de produzirem substâncias neuroquimicamente ativas, capazes de mediar a reposta inflamatória e exercer atividade terapêutica nas lesões do sistema nervoso central 20 .…”
Section: Introductionunclassified